Pelatihan Manajemen Keuangan Sebagai Peningkatan Daya saing bagi Pelaku Usaha Mikro di Kelurahan Sampangan - Purwatiningtyas Purwatiningtyas; Retnowati Retnowati; Sri Mulyani; Askar Yunianto (IKRA-ITH ABDIMAS, 2023)
The purpose of the community service program (PKM) is to provide knowledge and skillsregarding financial management to MSME players in the Sampangan area, especially MSME in RT05 RW VI, A special Target to provide training and guidance in improving financial managementand competitiveness. The majority of participants in community service activities are housewiveswho have businesses in order to increase family income . MSME development prospects are assessedbased on financial analysis. This PKM program activity disseminates to MSME actors, preparesequipment that supports the success of PKM, guides MSME actors in preparing financial statements,conducts training to improve knowledge, monitor and evaluate activities to support the success andsustainability of the business.